How to Scrutinize the Market God: Evaluating the Neo-Liberal Market Analogy Through Debates in Philosophy of Religion - Boyd, Jerome (Stance: an international undergraduate philosophy journal, 2020)
This essay aims to construct and demonstrate an analogical inter-disciplinary methodology. Developing the parallels between the God of classical theism and the modern market illustrated by Harvey Cox, I propose that neo-liberalism may be scrutinized as a philosophically understood entity. Debates within philosophy of religion may act as templates of scrutiny against the postmodern deity that is the neo-liberal market system. I aim to exemplify this method through the bedrock theological issue that is the Epicurean Paradox; just as philosophers produce theodicy, I contend that free-market fundamentalists need advocate laissez-faire in light of socio- economic suffering.